Urinary bladder paragangliomas: How Immunohistochemistry can assist to identify patients with SDHB germ line and somatic mutations - Giubellino, Alessio (Am J Surg Pathol, 2015)
Urinary bladder paraganglioma (paraganglioma) is a rare tumor of chromaffin cells of the sympathetic system of the urinary bladder wall. We studied 14 cases of this entity and investigated the usefulness of SDHB protein staining by immunohistochemistry (IHC) as a diagnostic tool to identify patients with bladder paragangliomas that could be associated with SDHB gene mutations, since these patient have a more aggressive disease. Eleven tumors from these patients were stained by IHC. Six out of 11 tumors were negative for SDHB staining by IHC with no cytoplasmic staining in tumor cells when compared with normal tissues. Five out of these 6 negative cases were confirmed to be positive for germline SDHB mutations. One case showed negative staining and no germline SDHB mutation, however, further investigation of the tumor revealed a somatic SDHB gene deletion. The remaining 5 cases showed strong cytoplasmic staining but they were negative for the presence of SDHB mutation. They were found to be either sporadic tumors or part of von Hippel-Lindau syndrome. Staining for SDH-A was positive in all cases. Our study confirms that there is very good correlation between the presence of an SDHB mutation, whether germline or sporadic, and negative SDHB IHC staining in urinary bladder paragangliomas, and represents the first study to demonstrate that somatic mutations can be recognized by IHC staining.